Normality and Regularity in Soft Ideal Spaces - A. Selvi (Mathematics and Computer Science: Contemporary Developments Vol. 4, 2024)
This article deals with the correspondence between soft ideal topological spaces and ideal topological spaces. Here, we recall some definitions and results that are useful in the sequel. A soft ideal on a non-empty set X is a non-empty collection of soft subsets with heredity property which is closed under finite unions. The focus of our study is on the concept of soft \(I_π g\) - normality and soft \(I_π g\) - regularity by the definition of soft ideal and various characterizations and properties are given. Furthermore, we present the behaviors and features of soft mildly normal spaces and soft almost regular spaces. This study will help the researchers to conduct further studies on soft ideal topological spaces.